Effects of variables on bipolymer production in 20l batch stirred tank fermentations - Mohd Firdaus, Hashim (2010)
This research is conducted to study the effects of variables on polyhydroxybutyrate(PHB) production in 20L batch stirred tank fermentations by using Cupriavidus necator. It consist of three major phases starting with scale up process, followed by fermentation process and mathematical analysis. The fermentation process is scaled up from the optimum condition in 500mL shake flask to 20L stirred tank bioreactor by approximating the set point values of air flowrate and agitation speed which gives the same dissolve oxygen tension (DOT) curve versus time. The closest DOT curve pattern to that of the optimum condition in 500mL shake flask is achieved by the combination 230 RPM agitation speed and 10L/min compressed air flowrate. This experiment is followed with fermentatin process involving the manipulation of the parameters agitation speed, temperature and initial glucose concentration. The 23 factorial experiment method is used to design the experiment around the set points of agitation speed and air flowrate which gave the optimum DOT curve. Among the experimental points, it is found that the highest yield of PHB is produced in condition of 210RPM agitation speed, 32! temperature and 23g/L initial glucose concentration. This experiment was followed by mathematical analysis using Yates’ Method to study the main effect and interactive effect of changing the level of experimental variables. The calculation proved that temperature has the biggest main effect on PHB production while the biggest interactive effect is from the combination of agitation speed and initial glucose concentration.